Dynamics of Pyricularia oryzae population race structures from 2003 to 2017 in Jiangsu province, China - Qi, Zhongqiang; Du, Yan; Liu, Muxing; Yu, Junjie; Zhang, Rongsheng; Yu, Mingna; Cao, Huijuan; Song, Tianqiao; Pan, Xiayan; Liang, Dong; Liu, Yongfeng (MDPI, 2022)
Rice blast, caused by Pyricularia oryzae, is one of the most destructive rice diseases worldwide. It is essential to understand the population structure and race distribution of P. oryzae for the prevention and control of rice blast. This study collected 1584 isolates across Jiangsu province from 2003 to 2017 to determine race diversity, common and dominant race structures, and resistance profiles using eight parameters from the Chinese differential cultivars (CDC) entries. Race diversity analysis indicated that the race diversity of 1584 isolates in Jiangsu province increased from 2003 to 2006 and fluctuated steadily from 2007 to 2017. Common race structure analysis showed that the common race structure of the isolates fluctuated wildly on an annual basis. Moreover, the race ZG1 was the dominant race, suggesting that the most commonly grown rice varieties in Jiangsu are highly adaptive to race ZG1. In addition, due to a higher level (>85%) of resistance to the population of isolates from 2003 to 2017, Tetep may be conformed as the most promising donor of blast resistance for resistance breeding in Jiangsu province. In summary, it is beneficial to control rice blast by continuous monitoring of the population structure and distribution of P. oryzae with the monogenic germplasm entries and by maintaining a diversity of rice varieties.